A Characterization Method for Coupling Relation in Multi-Infeed HVDC System - Xiao LEI; Xu SUN; Weiwei WANG; Lin LIU; Xinnian LI; Guangheng PANG (Zhongguo dianli)
At present, many HVDC/UHVDC projects are feeding into the East China Power Grid, and the interaction and coupling between AC and DC systems are complex. In order to characterize the coupling relation of multiple DC systems, an AC voltage distortion coupling coefficient of multi-infeed HVDC (ACDCC)is proposed. By calculating the bus AC voltage distortion of one inverter station caused by other HVDC system’s internal fault, the coupling coefficient of multiple DC systems is obtained, which covers an integrated assessment of such factors as the influence of DC transmission capacity on the AC system, the different response characteristics of HVDC control and protection system with different technical routes, and the AC system impedance characteristics between inverter stations. The concept of coupling area is put forward using coupling coefficient, which can be used to evaluate the simultaneous commutation failure risk of multi-infeed HVDC systems. A simulation verification is carried out on the multi-infeed system of East China Power Grid, and the results show that the proposed coupling coefficient and the characterization of coupling areas are basically consistent with the actual power system conditions. Therefore, the coupling coefficient can provide an important technical reference for the planning and operation of DC systems.